Pablo Antoñana y la historia: Noticias de la Segunda Guerra Carlista - Muro Jurío, Antonio (Huarte de San Juan. Geografía e Historia, 2009)
The writer Pablo Antoñana (1927- 2009), author of novels, short stories, journalistic articles and texts of various genres, set many of his stories in the historical past, in the long period that occupies the 19th century and first half of the 20th, showing special interest in military conflicts (the Carlist Wars and the Spanish Civil War) which occurred in the south-west of Navarra, a territory which forms the geografical reference of the fictional location of many of his works of fiction. Furthermore, in the last two decades of his life wrote several works with autobiographical, ethnographic and historical contents, with Noticias de la Segunda Guerra Carlista the most prominent among the latter. This book is an historical essay, with an informative intention, which, based on data collected mainly from municipal archives (to which the writer had access for his work as secretary of council), trying to reflect the point of view that the most humble participants had, that is, volunteers and farmers, in the last Carlist War (1872-1876). To this end, the narrator-historian produces a narrative discourse with literary resources that develop textual polyphony, which includes both the voices of the participants (who wrote records, letters, receipts, statements, proclamations, etc. in that conflict), as the author’s point of view, which emphasizes the connections between the last Carlist War and the Spanish Civil War.